Changes in the menu of manipulation: Electoral fraud, ballot stuffing, and voter pressure in the 2011 Russian election. (March 2016) - Harvey, Cole J.
Abstract: Vote-buying and voter intimidation are costly, complicated, and risky ways to manage elections. Why, then, do hybrid regimes utilize such tactics rather than ballot stuffing or election falsification? Such methods to mobilize voters require the construction of patronage networks that can be used to mobilize or demobilize clients beyond the election, and to display the incumbent's organizational strength. These networks are most valuable in places where opposition groups are active; consequently direct voter pressure should be more common in competitive areas. This paper uses data from Russia's 83 regions during the 2011 election to compare patterns of extra-legal mobilization with patterns of ballot stuffing and falsification. I conclude that local political competitiveness structures the mix of electoral manipulation tactics employed. Highlights: I theorize that voter pressure in hybrid regimes is more likely in competitive areas. Measures of three different election manipulation tactics are proposed. The correlates of these measures are estimated for each of Russia's 83 regions. Data from 94, 000 + polling places in the 2011 Russian legislative election is used. Political competitiveness structures the mix of tactics used to manage elections.